Molecular Detection and Distribution of Six Medically Important Vibrio spp. in Selected Freshwater and Brackish Water Resources in Eastern Cape Province, South Africa - Abioye, Oluwatayo E.; Osunla, Ayodeji Charles; Okoh, Anthony I. (Frontiers in Microbiology, 2021)
Water resources contaminated with pathogenic Vibrio species are usually a source of devastating infection outbreaks which has been a public health concern in both developed and developing countries over the decades. pPresent study assessed the prevalence of six medically significant Vibrio species in some water resources in Eastern Cape Province, South Africa, for twelve months. using standard methods. We detected vibrios in all the 194 water samples analyzed using polymerase chain reaction (PCR). The prevalence of V. cholerae, V. mimicus, V. fluvialis, V. vulnificus, V. alginolyticus and V. parahaemolyticus in freshwater samples was 34%, 19%, 9%, 2%, 3%, 2% and that of brackish water samples was 44%, 28%, 10%, 7%, 46% and 51% respectively. The population of the presumptive Vibrio spp. isolated from freshwater (628) and brackish water (342) samples that were confirmed by PCR was 79% (497/628) and 85% ( 291/342) respectively. Twenty-two per cent of the PCR-confirmed vibrio isolates from freshwater (n = 497) samples and forty-one per cent of the PCR-confirmed vibrio isolates from brackish water samples (n = 291) fall among the Vibrio species of interest.. The prevalence incidences of V. cholerae, V. mimicus, V. fluvialis, V. vulnificus, V. alginolyticus and V. parahaemolyticus amidst these Vibrio spp. of interest that were recovered from freshwater samples were 75%, 14%, 4%, 6%, 1% and 1% whilst that for brackish water samples were 24%, 7%, 3%, 3%, 47%, 3% and 18% respectively. Our observation during the study suggests pollution as the reason for the unusual isolation of medically important vibrios in winter. Correlation analysis revealed that temperature drives the frequency of isolation while salinity drives the composition of the targeted vibrio species at our sampling sites. The finding of the study is of public health importance going by the usefulness of the water resources investigated. Although controlling and preventing most of the factors that contribute to the prevalence of medically important bacteria such as Vibrio species at the sampling points might be difficult, regular monitoring for creating health risk awareness will go a long way to prevent possible Vibrios-related infections outbreaks at the sampling sites and their immediate environment.